PENGARUH PENGGUNAAN UMPAN IKAN LAYANG (Decapterus spp ) DAN IKAN TEMBANG (Sardinella spp) PADA ALAT TANGKAP LONGLINE KM. PEREMATA 318 TERHADAP HASIL TANGKAPAN IKAN TUNA DI PERAIRAN WPP 573 - Agustinus A H Ratung; Jey Ratu Amah; Mukhlis Ali; Edizul A Sadir (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2025)
This study aims to determine the effect of differences in the use of scad (Decapterus spp.) and scad (Sardinella spp.) bait on tuna catches using longline gear in Fisheries Management Area (WPP) 573. The research method used was a field experiment with a quantitative approach. The study was conducted over 16 fishing operations. The results showed that the use of scad bait resulted in higher tuna catches than scad bait. The average catch using scad was 1,206 kg per fishing operation, while the average catch using scad was 618 kg per fishing operation. Statistical analysis using the t-test showed a significance value of p <0.05, indicating a significant difference between the two types of bait on catches. The conclusion of this study is that scad bait is more effective in increasing tuna catches using longlines in the waters of WPP 573.